2021
DOI: 10.1155/2021/4919410
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extract of Pomegranate (Punica granatum) Peel in Increasing the Expression of Caspase-3 in DSS-Induced Mice

Abstract: Background. Colorectal cancer (CRC) is a malignancy derived from the glandular epithelial cells in the colon. Patients with inflammatory bowel disease (IBD) are more likely to develop CRC. Cancer proliferation is characterized by the loss of inhibition of apoptosis, which involves caspase-3 activation. This study examined the effects of the pomegranate peel extract on the expression of caspase-3 in mice crypt cells induced by dextran sodium sulfate (DSS) 2%. Methods. The experimental study was done in six grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In line with these findings, it was recently reported that PE extract increased caspase-3 expression in an animal model of colorectal cancer, which promoted apoptosis machinery (Kusmardi et al, 2021). A similar influence of pomegranate peel extract on caspase-3 was also observed in the hepatocellular carcinoma cell model in which the extract was able to induce elevation of caspase-3 and enhance apoptosis (Elbakry et al, 2023).…”
Section: Discussionsupporting
confidence: 69%
“…In line with these findings, it was recently reported that PE extract increased caspase-3 expression in an animal model of colorectal cancer, which promoted apoptosis machinery (Kusmardi et al, 2021). A similar influence of pomegranate peel extract on caspase-3 was also observed in the hepatocellular carcinoma cell model in which the extract was able to induce elevation of caspase-3 and enhance apoptosis (Elbakry et al, 2023).…”
Section: Discussionsupporting
confidence: 69%
“…This enzyme is responsible for maintaining genomic integrity and is required to cut both DNA strands, as well as to ensure proper DNA replication and chromosome segregation; hence, polyphenols are described as a potent topoisomerase II poisons [52]. Kusmardi et al showed that the ethanolic extract of pomegranate induced apoptosis by increasing caspase-3 expression [53]. Another study conducted by Ahmed et al demonstrated the antitumor activity of pomegranate peel extracts in CRC through the down-regulation of the Wnt/β-Catenin pathway, whose target genes play an ultimate role in tissue homeostasis, as well as in the initiation and progression of CRC through the regulation of various cellular processes, including proliferation, stem cell fate, survival, differentiation, migration, and angiogenesis [54].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed several promising research and development Chinese herbal medicines for the therapy of IBD, including turmeric, frankincense, and pomegranate peel. [30][31][32] Among them, frankincense, a phytomedicine whose main component is the compound of boswellic acid, has long been used in the treatment of inflammatory diseases. [33] Clinical studies and practices have shown that frankincense, in addition to its antioxidant and anti-inflammatory effects, has the effects of regulating human lipid metabolism, antiulcer, and regulating human immunity.…”
Section: Akba Alleviates Dss-induced Inflammatory Injury In Ibd Mice ...mentioning
confidence: 99%